Surface Impedance for Real-Time Cardiac Monitoring in Body Area Networks - Khaoula Tayari; Imen Jarraya; Omar Cheikhrouhou; Anis Koubaa; Hamadi Ghariani (IEEE Access)
Biomedical electronics are becoming increasingly important as a result of concerns with remote patient monitoring. It is becoming increasingly vital to follow cardiac patients outside of hospitals and in their daily lives. Therefore, wireless communication and home usage are suitable for medical devices. This study proposes an innovative technique for monitoring cardiac activity based on variation in surface impedance during cardiac muscle activity. A human thoracic model was rigorously created to justify our approach, confirming efficiency of the technique. This model has a three-layered structure, with each layer distinguished by its distinct surface impedances. As one moves from the deepest to the outermost layer, the impedance of each layer changes. Therefore, it is crucial to understand the physical properties of biological tissues to predict their activity accurately. This work introduces an implementation of a novel approach, centered on analyzing the surface impedance variation within a multilayer model. This variation is intricately linked to the thickness of the innermost layer within the ISM band across four distinct frequencies: 433 MHz, 915 MHz, 2.4 GHz, and 5.8 GHz. These frequencies provide a balance between range, reliability, and compatibility with existing wireless technologies, ensuring effective and robust communication for applications.